MANAGEMENT ACCOUNTING PRACTICES AT IMANUEL CHURCH IN GORONTALO CITY - Meifana Putri Kalengkongan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze and describe the management accounting practices applied at Imanuel Church in Gorontalo City as a nonprofit organization. The dimensions examined include budget planning, internal control, financial reporting, and the evaluation of financial performance and ministry programs. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Research informants consisted of the Head of BPHMJ (Daily Working Body of the Congregation Council), the Treasurer, the Secretary, and Church Officials directly involved in financial management. The findings indicate that management accounting practices at Imanuel Church have not yet functioned optimally: (1) budget planning lacks a structured and documented annual budget system; (2) internal control does not yet apply the principle of segregation of duties and has no formal internal audit mechanism; (3) financial reporting is limited to recording cash inflows and outflows and does not comply with ISAK 35; and (4) performance evaluation does not use measurable indicators and no comparison between budget and realization has been conducted. Strengthening of a structured financial management system in accordance with applicable accounting standards is needed.